Bakar Line Services : Fire Prevention System / Ahmad Naim Asfandi ...[et al.] - Asfandi, Ahmad Naim; Badlissah, Ameer Syafiq; Abd Halin, Mohamad Nur Naquib; Abdullah, Mohammad Faquaruddin; Khairul Tazman, Khairul Faizal (2016)
Bakar Line Services is a service company that sales fire prevention product like fire alarm system and fire exteinguisher. We also provide maintaince and after sales services to our customer. Johor Bahru facing a growth in development of modernization. High demand of the service of loss and fire prevention company to install a fire alarm system to the new develop building. This is the company opportunity to show what we have up on our sieves, as new building is looking for good and quality services from loss and fire prevention company. With the best set of skills and reasonable price of the packaged on offer, surely the customers cannot resist. By focusing on high quality customer services and continuous development of company's skills, our company will try to compete with other competitor in this industry. Our goal is to expand our company outside Johar Bahru like Kuala Lumpur or Singapore in 10 years. To achive it, the company have to work hard to maintain the customers satisfication.